2007
DOI: 10.1021/jm060747l
|View full text |Cite
|
Sign up to set email alerts
|

1,4-Benzodiazepines as Inhibitors of Respiratory Syncytial Virus. The Identification of a Clinical Candidate

Abstract: Respiratory syncytial virus (RSV) is the cause of one-fifth of all lower respiratory tract infections worldwide and is increasingly being recognized as representing a serious threat to patient groups with poorly functioning or immature immune systems. Racemic 1,4-benzodiazepines show potent anti-RSV activity in vitro. Anti-RSV evaluation of 3-position R- and S-benzodiazepine enantiomers and subsequent optimization of this series resulted in selection of a clinical candidate. Antiviral activity was found to res… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
43
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 48 publications
(47 citation statements)
references
References 25 publications
(82 reference statements)
0
43
0
2
Order By: Relevance
“…An early derivative, A-57400, showed improved activity but also showed some growth inhibitory effects at 50 M. Separation of the two isomers of A-33903 demonstrated that the antiviral activity was associated with the S enantiomer (15). Therefore, all subsequent compounds of this series tested were the isolated S enantiomers.…”
Section: Profile Of Rsv604mentioning
confidence: 96%
“…An early derivative, A-57400, showed improved activity but also showed some growth inhibitory effects at 50 M. Separation of the two isomers of A-33903 demonstrated that the antiviral activity was associated with the S enantiomer (15). Therefore, all subsequent compounds of this series tested were the isolated S enantiomers.…”
Section: Profile Of Rsv604mentioning
confidence: 96%
“…The synthesis of new 1H-imidazole-4,5-dimethyl dicarboxylate (1-4), 1H-imidazole-4,5-diamide (5)(6)(7)(8), imidazole [4,5-e] [1,3]diazepine-4,8-dione (9-11) and acyclic carbamoyl imino-ureido imidazole derivatives (12 and 13) is performed according to the Figure 2. [4,5-e] [1,3]diazepine-4,8-dione (9-11) and ureido-imino-carbamoyl-imidazole derivatives (12-13).…”
Section: Chemistrymentioning
confidence: 99%
“…There is a clear need for new anti-RSV therapeutics, with improved efficacy and safety for broader applications [3]. Powell and his colleagues have recently identified a new class of RSV inhibitors, namely 1,4-benzodiazepines [4], which eventually led to identification of RSV604 as a clinical candidate [5].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Virazole has shown equivocal efficacy in bone marrow transplant patients and is not typically used to treat infants with RSV due to poor efficacy and tolerability, as well as the complexity of the specialized aerosol drug delivery system (14)(15)(16). A number of small-molecule inhibitors of RSV have been evaluated as potential therapeutics for treating RSV infections that target viral entry and replication (17)(18)(19)(20)(21)(22)(23). While several clinical candidates have been evaluated in human studies, only ribavirin has been approved for the treatment of RSV infection.…”
mentioning
confidence: 99%